The Medical Periodicals of J.C. Tode and the Idea of Public Health. Issue 1 (1st January 2017) - Eriksen, Anne
Abstract : In 1770 'Den medicinske Tilskuer' (The Medical Spectator) was published in Copenhagen. The man behind it was the surgeon, physician and poet Johann Clemens Tode. This was the first of 16 journals in total on health and medicine that Tode was to write, edit and publish until his death in 1806. With his journals, Tode contributed significantly to making health a public issue. This implies conceptualizing health and medicine as reaching beyond the private sphere and individual lives, to rather concerning society at large. To understand the late 18th century, it is equally important to see that the idea of 'public health' also implies the existence of a public sphere. The article argues that Tode's journals contributed to the making of such a public and that he did so by addressing its health. It investigates how the readers and – more generally – the public were staged and produced in Tode's medical periodicals. The object of investigation is not primarily the medical advice given by Tode as much as the way it is given, the figures or personae that it is given to and the public that it helped to create.